Diagnosis and management of fecal incontinence in children and adolescents - Shen, Zhe-Ying; Zhang, Jin; Bai, Yu-Zuo; Zhang, Shu-Cheng (Frontiers in Pediatrics, 2022)
Fecal incontinence (FI) is a commonly occurring disease of high concern. It is characterized by voluntary and involuntary defecation in children and adolescents. It is not only a physical disease but also a psychological and behavioral disorder. FI poses a serious burden on individuals and their families and therefore has become a social problem. Unfortunately, the management of FI among children is still a challenge because the etiology varies widely. Constipation has been found to be the most common cause, while sphincter dysfunction and neurogenic abnormalities may also play a role. Currently, no consensus guidelines exist, and the criteria for selecting optional methods remain unclear. It is therefore necessary to improve the efficacy of diagnosis and management strategies of FI in children. This review focused on the classification and etiology, discussed the diagnosis and management methods of FI in children and adolescents, and aimed to guide future studies.